Radiomorphology of the Habib Sealer-InducedResection Plane during Long-Time Followup:A Longitudinal Single Center Experience after 64 Radiofrequency-AssistedLiver Resections. (4th August 2010) - Kleinert, Robert; Wahba, Roger; Bangard, Christoph; Prenzel, Klaus; Hölscher, Arnulf H.; Stippel, Dirk
Abstract : Background . Radiofrequency (RF-) assisted liver resection devices like the Habib sealer induce a necrotic resection plane from which a small margin of necrotic liver tissue remains in situ. The aim of the present paper was to report our long-time experience with the new resection method and the morphological characteristics of the remaining necrotic resection plane. Methods . 64 RF-assisted liver resections were performed using the Habib sealer. Followup was assessed at defined time points. Results . The postoperative mortality was 3, 6% and morbidity was 18%. The followup revealed that the necrotic zone was detectable in all analyzed CT and MRI images as a hypodense structure without any contrast enhancement at all time points, irrespectively of the time interval between resection and examination. Conclusion . Liver resection utilizing radiofrequency-induced resection plane coagulation is a safe alternative to the established resection techniques. The residual zone of coagulation necrosis remains basically unchanged during a followup of three years. This has to be kept in mind when evaluating the follow up imaging of these patients.